It's not the how or the what but the who : - Fernandez Araoz, Claudio (Harvard Business Review Press, 2014)
Succeed by mastering the art of the who Why surround yourself with the best? Because it matters-in all aspects of life. In fact, in professional environments, getting people right-what global leadership authority Claudio Fernandez-Araoz calls "the art of great; who' decisions"--Marks the difference between success and failure. To thrive, you need to identify those with the highest potential, get them in your corner and on your team, and help them grow. Yet surprisingly very few of us are able to meet that challenge. This series of short and engaging essays outlines the obstacles to great "who" decisions and offers solutions to address them in a systematic way. Drawing from several decades of experience in global executive search and talent development, as well as the latest management and psychology research, Fernandez-Araoz offers wisdom and practical advice to improve the choices we make about employees and mentors, business partners and friends, top corporate leaders and even elected officials.